Organizational Alignment and IT Governance Using COBIT 2019 Goals Cascade: Keselarasan Tujuan Organisasi dan Tata Kelola Teknologi Informasi Menggunakan Goals Cascade COBIT 2019 - Turangan, Bravo; Sentinuwo, Steven Ray; Kaunang, Sumenge Tangkawarouw G. (Universitas Sam Ratulangi, 2025)
Abstract — Information technology (IT) governance is a crucial factor in ensuring that IT investments are aligned with organizational objectives, improve operational efficiency, and mitigate risks. This study focuses on the Regional Education Office of North Sulawesi Province, which plays a strategic role in improving the quality of secondary and special education services. The Strategic Plan for 2025–2029 explicitly supports the provincial government’s mission to improve human resource quality through equitable and quality education. However, the 2024 SPBE evaluation revealed significant weaknesses in governance and management domains, indicating that IT implementation remains suboptimal and prone to information system fragmentation. This study aims to map the organization’s vision, mission, and objectives into the Goals Cascade mechanism of the COBIT 2019 framework. A mixed methods approach, combining qualitative and quantitative analysis was applied through the identification of stakeholder drivers, stakeholder needs, enterprise goals, alignment goals, and governance and management objectives. The novelty of this research lies in the comprehensive application of the COBIT 2019 Goals Cascade to determine priority IT governance objectives in the regional education sector. The results indicate a primary focus on objectives supporting application integration, management information quality, and acceleration of digital transformation. The study concludes that COBIT 2019 provides an effective foundation for formulating aligned IT governance strategies supporting the 2025–2029 Strategic Plan. Keywords — COBIT 2019; Goals Cascade; IT Governance; Digital Transformation in Education Abstrak — Tata kelola teknologi informasi (TI) merupakan faktor krusial untuk memastikan investasi TI selaras dengan tujuan bisnis, meningkatkan efisiensi operasional dan memitigasi risiko. Penelitian ini berfokus pada Dinas Pendidikan Daerah Provinsi Sulawesi Utara yang memiliki peran strategis dalam peningkatan mutu pendidikan menengah dan layanan khusus. Rencana Strategis Dinas Pendidikan Daerah Provinsi Sulawesi Utara Tahun 2025–2029 secara eksplisit mendukung misi pemerintah daerah dalam meningkatkan kualitas sumber daya manusia melalui pendidikan berkualitas yang merata. Namun, hasil evaluasi Sistem Pemerintahan Berbasis Elektronik (SPBE) Provinsi Sulawesi Utara tahun 2024 menunjukkan kelemahan signifikan pada domain tata kelola dan Manajemen SPBE, yang mengindikasikan implementasi TI belum optimal dan berpotensi menimbulkan fragmentasi sistem informasi. Penelitian ini bertujuan memetakan visi, misi dan tujuan organisasi ke dalam mekanisme Goals Cascade pada framework COBIT 2019. Metode penelitian yang digunakan adalah metode campuran atau pendekatan kualitatif dan kuantitatif melalui tahapan identifikasi stakeholder drivers, stakeholder needs, enterprise goals, alignment goals dan governance and management objectives. Kebaruan penelitian ini terletak pada penerapan Goals Cascade COBIT 2019 secara menyeluruh untuk mengidentifikasi prioritas objektif tata kelola TI di sektor pendidikan daerah. Hasil penelitian menunjukkan perlunya fokus pada objektif yang mendukung integrasi aplikasi, peningkatan kualitas informasi manajemen, dan percepatan transformasi digital. Simpulan penelitian menegaskan bahwa COBIT 2019 efektif sebagai dasar perumusan strategi tata kelola TI yang selaras dengan Renstra 2025–2029. Kata Kunci: COBIT 2019; Goals Cascade; Tata Kelola Teknologi Informasi; Transformasi Digital Pendidikan.